Apocrine Breast Carcinoma with Thanatosomes (Hyaline Globules) - Mitsuhiro Tachibana; Masashi Nozawa; Tadahiro Isono; Kei Tsukamoto; Kazuyasu Kamimura (Diagnostics)
Thanatosomes (hyaline globules or death bodies) are histologically observed in various non-neoplastic and neoplastic conditions. Some of these globules are associated with apoptotic cell death. Only six documented cases of thanatosomes have been reported in breast tumors. In this rare case involving a 64-year-old Japanese woman diagnosed as having rectal cancer, preoperative computed tomography scanning revealed breast cancer in her right breast. Following a right total mastectomy, a tumor characterized as apocrine carcinoma (carcinoma with apocrine differentiation) containing thanatosomes was discovered. These globules are PAS positive and diastase resistant, exhibit deep fuchsinophilic staining with Masson’s trichrome, stain dark blue with PTAH, and are negative for mucin by Alcian blue. The tumor cells tested positive for the androgen receptor, FOXA1, and GCDFP15. Human epidermal growth factor type 2 (HER2)/neu score was 3+/positive, and the Ki-67 labeling index was 60%. Thus, the tumor represented high-grade, HER2-enriched apocrine carcinoma. Thanatosomes are immunoreactive to cleaved caspase-3 and are histological markers of high cell turnover and apoptotic cell death. Therefore, in this nonspecific microscopic neoplastic condition, they are typically linked to high-grade tumors, as this case showed. This report presents a rare case of apocrine breast cancer featuring a limited number of thanatosomes.